Detection of multidrug-resistant Salmonella in native chickens by culture, polymerase chain reaction, and enzyme linked immunosorbent assay - Balala, Lotis M.; Mendoza, Bernadette C.; Baldrias, Loinda R.; Masangkay, Joseph S. (Asia-Pacific Journal of Science and Technology, 2024)
A compromise in biosecurity measures is a major determinant of pathogen emergence in free-range animals. This study aimed to detect antimicrobial-resistant Salmonella in free-range Philippine native chickens. Clinical and environmental samples were collected from a free-range farm with 50 Banaba x Paraoakan native chickens to analyze Salmonella using conventional culture, polymerase chain reaction (PCR), and enzyme-linked immunosorbent assay (ELISA). Antimicrobial resistance was confirmed through the agar disc diffusion method. Salmonella persisted in poultry samples from Day 10 to Day 150 with an overall detection rate of 8.9% (21/237). The earliest detection of Salmonella was on Day 10 by conventional culture and on Day 30 by PCR posing a detection rate of 2.11% (5/237) and 8.04% (16/199), respectively. ELISA detected seropositivity on Day 120 with an overall seroconversion rate of 60%. Antibiotic resistance of isolates was 80% in ampicillin, doxycycline, tetracycline, and trimethoprim-sulfamethoxazole; 60% in kanamycin and cefuroxime; and 40% in neomycin. Eighty percent (4/5) of the isolates demonstrated a potential multidrug resistance pattern. Multidrug resistant Salmonella persisted in free-range native chickens posing food quality and safety implications. Biosecurity and preharvest strategies should be improved to reduce the pathogen in free-range farming.